Diskursus Epistemologi Tafsir Isyãrĩ Dan Tafsir Bathini - T. Mairizal (ISTIFHAM, 2024)
The Isyari interpretation, often taken by Sufi scholars, can be classified into one of the divisions of interpretation according to its source. This category includes the interpretations by al-Ma'tsũr (interpretation based on tradition) and bi ar-ra'y (interpretation based on logic). The Isyari interpretation is pursued by exploring the implicit or inner meanings in the Qur'an. However, the interpretation of Sufi groups fundamentally differs from the interpretation of the Bãthiniyyah group, although both seek to uncover the inner meanings of the Qur'an. Understanding the Qur'an by delving into implicit meanings is not a new issue in the Islamic treasury. Still, it has emerged since the companions' time and continued to evolve in subsequent periods. Several verses of the Qur'an and hadith also depict that the Qur'an can be understood explicitly and implicitly. Nevertheless, the controversy about Sufi interpretation continues; some allow it, while others condemn it.